Dissemination of the splatter generated during resin-based and glass ionomer sealant application procedures - Horsophonphong, Sivaporn; Malulim, Sarawdee; Yuthanarong, Ornrumpa; Tuwaemah, Tuansuraiya; Siribunlong, Nitasneem; Nakornchai, Siriruk (Mahidol Dental Journal, 2022)
Objectives: The aim of this study was to compare the dissemination of the splatter generated during resin-based and glass ionomer sealant application procedures. Materials and Methods: The experiment was conducted on a dental phantom head that was inserted into the head rest of a dental chair and set in a reclined position, mimicking the sealant application procedure routinely performed on a patient. To trace the dissemination of splatter droplets generated during the sealant application procedure, a 0.1% fluorescein dye solution was connected to the dental unit water supply and a 1 x 1 ft2 cotton sheet, with a hole in the middle for the mouth, was placed on the phantom’s head. Resin-based and glass ionomer sealant application procedures were performed on the right and left posterior teeth by four operators. After the sealant application procedure was completed and the fluorescent stain was completely dried, a transparent grid with 0.5x0.5 cm2 squares was placed over the cotton sheet and the number of squares with splatter stain visible through the grid was counted under ultraviolet light by two examiners who were blinded to the treatments. The examiners performed intra- and inter-correlation tests for reliability. Results: The splatter production varied among the operators. There was no significant difference between the number of contaminated squares generated from the glass ionomer sealant and resin-based sealant application procedures (p>0.05). Moreover, the number of contaminated squares was not significantly different between the two sealant materials’ applications on the same treatment side (p>0.05). Conclusion: The application process of the resin-based and glass ionomer sealant generated the same level of splatter dissemination.